Pemberdayaan Ekonomi Masyarakat Pada Komunitas Henna Kecamatan Mersam Kabupaten Batang Hari - Intan Tri Nanda; Rofiqoh Ferawati; Muhammad Subhan (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
. This research is motivated by community economic empowerment in the henna community. The term empowerment means strengthening, an effort to actualize the potential that is already owned by the community. The purpose of this research is to find out: (1) Henna is made one of the sources of income in community economic empowerment in the henna community. (2) The henna community in Mersam sub-district has very few members, and does not understand the management of its economic empowerment efforts in the field of henna services. This research is a qualitative description research, with the subjects, namely, the henna community, henna services, and community economic empowerment in the object area of Mersam sub-district. The data analysis technique uses interactive analysis with steps, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that: (1) Henna is made one of the sources of income in community economic empowerment in the henna community. That is, with efforts to increase economic awareness, creativity, develop or empower the community economy. (2) The obstacles faced by the henna community as a source of income. Namely, information provision, community institutional development, efforts to improve the economy in the henna community.